Petit voyage en tram ou quand le lexique et le style se véhiculent - Philippe Rapatel (Lexis: Journal in English Lexicology)
The reading of an excerpt of England, My England (“Tickets, please”) by D. H. Lawrence leads the reader into an adventurous journey where speed and pause, acceleration and slowing down, appeal and repulsion, relief and fear combine into a varied and eventful trip through the Midlands. The author makes use of all his art together with the means offered by language so as to take him/her on a small country train/tramcar. Our goal is to display and study the skilful range of stylistic devices, visual effects, pace, choice of metaphors and lexis implemented to give the story the most evocative dynamics.